2010
DOI: 10.1007/s11010-010-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PPARγ can down-regulate Skp2 expression in MDA-MB-231 breast tumor cells

Abstract: Skp2 is frequent amplified and overexpressed in breast cancer, making it a potential molecular target for cancer therapy. The objective of this study was to examine the effect of PPARγ overexpression on Skp2 expression in breast cancer cell lines. First, we investigated the role of PPARγ and Skp2 in human breast cancer progression. Immunohistochemical analysis of 70 specimens on formalin-fixed paraffin sections was performed. Furthermore in vitro, Western blot analysis was used to study the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…PPAR␥ is a ligand-activated transcription factor, a member of the nuclear hormone receptor (NHR) superfamily expressed in many tissues (Meng et al, 2010), it is a potent cell proliferation inhibitor through induction of cdk inhibitors, its expression was increased concomitantly when apoptosis occurred, treatment of cancer cells with PPAR␥ ligands led to growth inhibition and apoptosis of cancer cells (Liu et al, 2009;Meng et al, 2010). Cell cycle progression is accelerated by cyclins and decelerated by cyclin-dependent kinase (CDK) inhibitors, such as cyclin D1 and Rb, transition through G 1 into S phase requires the activation of cyclin D and cyclin E (Hu et al, 2002;Yoshida et al, 2010;Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ is a ligand-activated transcription factor, a member of the nuclear hormone receptor (NHR) superfamily expressed in many tissues (Meng et al, 2010), it is a potent cell proliferation inhibitor through induction of cdk inhibitors, its expression was increased concomitantly when apoptosis occurred, treatment of cancer cells with PPAR␥ ligands led to growth inhibition and apoptosis of cancer cells (Liu et al, 2009;Meng et al, 2010). Cell cycle progression is accelerated by cyclins and decelerated by cyclin-dependent kinase (CDK) inhibitors, such as cyclin D1 and Rb, transition through G 1 into S phase requires the activation of cyclin D and cyclin E (Hu et al, 2002;Yoshida et al, 2010;Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Skp2 was also revealed as a novel target for E2F regulation that is disrupted in several human tumor cell lines [56]. Additionally, over-expression of PPARγ (peroxisome proliferators activated receptor gamma) can down-regulate Skp2 expression in breast tumor cells [57]. BCR-ABL (breakpoint cluster region-abelson leukemia gene) controls Skp2 gene transcription via the PI3K/AKT/Sp1 pathway in leukemia cells [58].…”
Section: The Role Of Skp2 In the Development And Progression Of Prmentioning
confidence: 99%
“…Early reports demonstrated that Skp2 recognizes and targets cell cycle inhibitors p21 Cip1/WAF and p27 Kip1 , leads to their ubiquitination and degradation, and further causes cell cycle progression [3]. Skp2 is overexpressed and associated with poor prognosis in variety of human cancers, including prostate cancer [4], gastric cancer[5], breast cancer [6, 7], and liver cancer [8], suggesting the oncogenic role of Skp2 in tumorigenesis. However, the association between Skp2 and NPC development and prognosis still remains unclear [9].…”
Section: Introductionmentioning
confidence: 99%